2020
DOI: 10.21037/tcr-20-1073
|View full text |Cite
|
Sign up to set email alerts
|

Screening of hub genes associated with prognosis in non-small cell lung cancer by integrated bioinformatics analysis

Abstract: Background: Lung cancer is an intractable disease and the second leading cause of cancer-related deaths and morbidity in the world. This study conducted a bioinformatics analysis to identify critical genes associated with poor prognosis in non-small cell lung cancer (NSCLC).Methods: We downloaded three datasets (GSE33532, GSE27262, and GSE18842) from the gene expression omnibus (GEO), and used the GEO2R online tools to identify the differentially expressed genes (DEGs). We then used the Search Tool for Retriev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Metabolic pathways are a new emerging hallmark of lung cancer and are associated with disturbed carbohydrate metabolism ( Zhou et al, 2020 ). Non-alcoholic fatty liver disease is correlated with immune checkpoint inhibitor-related treatment strategies in patients with NSCLC with liver metastases ( Zeng et al, 2020 ). These findings indicated that the enriched pathways are substantially related to the carcinogenesis of LUSC.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic pathways are a new emerging hallmark of lung cancer and are associated with disturbed carbohydrate metabolism ( Zhou et al, 2020 ). Non-alcoholic fatty liver disease is correlated with immune checkpoint inhibitor-related treatment strategies in patients with NSCLC with liver metastases ( Zeng et al, 2020 ). These findings indicated that the enriched pathways are substantially related to the carcinogenesis of LUSC.…”
Section: Discussionmentioning
confidence: 99%
“…To established a prognostic system for cancer patients, cancer-related genes have been used to develop cancer panels in lung cancer (28), malignant lymphoma (29), melanoma (30), gastric cancer (31), and other cancers (32).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, based on some current biological information analysis, in some studies of non-small cell lung cancer, CDC 20 and CCNB2 are related to the survival rate of patients to a certain extent. Meanwhile, in cell experiments, the expression level of CCNB2 is also high in lung cancer [ [27] , [28] , [29] ]. In addition, as a heterogeneous disease.…”
Section: Discussionmentioning
confidence: 99%